Antagonistic Ability of Trichoderma sp. against Ganoderma sp. on Litter Medium of Acacia mangium - Samingan Samingan (Universitas Syiah Kuala, 2014)
Trichoderma sp are common fungi in the soil and play important role in decomposing of cellulose-rich. The distribution of Trichoderma sp (TBPH isolate) in litter layers of Acacia mangium was observed in two years’ old of health standing (2S) and Ganoderma sp-attacked standing (2G). The objectives of this research were to observe Trichoderma sp distributions in leaf litter layers and to determine of antagonistic ability of Trichoderma sp TBPH against Ganoderma sp (GBR isolate). Trichoderma sp in sawdust medium was spread above of F litter layer in 50 x 50 cm area. Total populations of Trichoderma were observed each month during eight months. Antagonistic activities of Trichoderma sp TBPH against Ganoderma sp GBR were tested by dual test method on PDA and PDA with litter powder (PDAS) media. The results showed that populations of Trichoderma sp were fluctuating and the highest population on both standings of F layer and were followed by H and L layers. Fluctuations of Trichoderma sp population on L layer were tended to follow rainfall fluctuations while those on F layer were tended to follow litter pH fluctuations. Antagonistic test showed that inhibition percentage of PDAS medium was lower than those of PDA medium indicating litter amendment on media being causes of lower antagonistic activities of Trichoderma sp.